Ropain Naach as Performance: The Intersection of Gender, Ritual, and Agrarian Culture in Western Nepal - Sapkota, Tikaram (Academia Journal of Humanities & Social Sciences, 2026)
This study has examined Ropain Naach, a paddy planting dance, traditionally being exhibited in the western town of Nepal through the perspective of performance studies. The dance enacted during the July planting season, involves male performers disguised as females as planting workers and other participants acting as diggers, who sing songs expressing desire for communal values and demonstrating true love while performing agricultural labor. Employing a qualitative interpretative method, primary data were taken from the text, "Ropain Naachamaa Patali Naani" (A slim girl in paddy planting dance) written by a local pioneer. The paper has specifically applied Schechner’s concept of restored behavior and Butler’s theory of gender performativity along with other relevant ideas to analyze how the dance transforms labor into symbolic, embodied, and affective performance. The findings indicate that Ropain Naach functions as a site for enacting gender, expressing emotional and romantic narratives, fostering social cohesion, and reinforcing cultural continuity. The study highlighted the dance’s dual roles as both ritualized agrarian practice and performative medium through which local knowledge, social norms, and communal identity are transmitted. By focusing on Baglung Bazaar as a specific context, this study addressed a gap in Nepali performance scholarship, underscoring the importance of documentation and preserving indigenous agrarian performances. The study contributes to visualize a local tradition to a broader context and that will be a source of scholarship for global citizens.